Broken bones, broken minds, and broken hearts: Psychotrauma resources for pediatric non-accidental trauma survivors – Editorial. (July 2021) - Lin, I-Chun; McKenny, Mark; Elkbuli, Adel
Highlights: The PTSD Checklist for DSM-5 (PCL-5) assessment is not meant for an acute trauma and is administered to assess PTSD symptoms experienced over the past month. This screening tool is indicated for children ages 7 or above, which spans a wider age range than does the PHQ-9. It is difficult to say how widely available psycho-trauma resources are in the acute care setting at PTCs. However, the literature demonstrates the importance of immediate, adequate psychologic care for pediatric trauma cases. We hope that trauma centers moving forward, stop only healing the broken bones and start healing the broken bones, the broken minds, and comforting the broken hearts.